O processo de preparação para o ENADE e seus impactos no trabalho docente: uma análise a partir da pedagogia histórico-crítica - MAXIMIANO, João Lucas de Souza (2022)
The present dissertation was carried out in the Postgraduate Program in Education of the Universidade do Oeste Paulista (UNOESTE) and is part of the research line “Public Policies in Education, training processes and diversity”. Educational policies should recognize educational work as an essentially human activity and respect its specificities, however, due to the prevailing neoliberal logic, instruments such as the National Student Performance Examination (ENADE) were subverted in favor of marketing aspirations. The objective of the study was to analyze the impacts caused by the process of preparation for ENADE in the teaching work in a private HEI (Higher Education Institution), located in the interior of the state of São Paulo. Based on the historical-dialectical materialist method, a systematic literature review was carried out in a database, a document analysis of Law no. 10.861/2004, which institutes the National Higher Education Assessment System (SINAES) and a field survey, using the following data collection instruments: semi-structured interviews with three coordinators; and application of questionnaires with twenty-five professors, both groups of participants belong to the area of Human Sciences. The investigated object presented four categories for analysis, they are: a) Impact of the preparation for ENADE with a focus on grade and ranking; b) Impacts of the reduced interpretation of ENADE on the guidelines of the private HEI; c) Impact of the divestiture and lack of critical positioning; d) Impact of preparation for ENADE on the intensification of teaching work. As the main results of the research, it is highlighted that ENADE has become the protagonist of SINAES and imposes itself in the daily life of HEIs, with an emphasis on private ones, resulting in concern and demand on the part of the Dean of Education. In the field study, it was possible to observe that the activities carried out in order to prepare students for ENADE, occur with emphasis on the classes that will be submitted to external evaluation, and most of the actions occur in parallel to the curriculum through of workshops and lectures. This process is hierarchically verified and results in the burden of professionals who find themselves in a scenario of excessive demands for good results in the external evaluation. It is important to point out that the participants of the investigated sample have a reduced understanding of educational policies and demonstrate a passive and uncritical position in relation to these practices that do not contribute to the educational work in favor of human emancipation through omnilateral training. Finally, as a result of alienating processes in higher education, the participants' testimonies do not indicate that the impacts of preparing for ENADE are essentially negative for educational practice, however, after unveiling the object of study through the analysis of its multiple determinations, it is possible to say that this process directly contributes to the intensification of teaching work, which may lead to increased pressure and professional suffering due to the productivity-quality dilemma.